-5-8(m-1)=-7+2m

Simplify each term.

Apply the distributive property.

-5-8m-8⋅-1=-7+2m

Multiply -8 by -1.

-5-8m+8=-7+2m

-5-8m+8=-7+2m

Add -5 and 8.

-8m+3=-7+2m

-8m+3=-7+2m

Subtract 2m from both sides of the equation.

-8m+3-2m=-7

Subtract 2m from -8m.

-10m+3=-7

-10m+3=-7

Subtract 3 from both sides of the equation.

-10m=-7-3

Subtract 3 from -7.

-10m=-10

-10m=-10

Divide each term in -10m=-10 by -10.

-10m-10=-10-10

Cancel the common factor of -10.

Cancel the common factor.

-10m-10=-10-10

Divide m by 1.

m=-10-10

m=-10-10

Divide -10 by -10.

m=1

m=1

Solve for m -5-8(m-1)=-7+2m